Evaluation of the Challenges of E-Government Implementation: Analysis of the E-Government Development Index in Indonesia - Nurhidayat, Nurhidayat; Nurmandi, Achmad; Misran, Misran (Jurnal Manajemen Pelayanan Publik, 2024)
The rapid development of information technology is the main driver for significant dynamics in the implementation of e-government. This study aims to present an analysis of the challenges of implementing e-government in Indonesia. This study used quantitative methods using secondary data. The results showed that the E-Government Development Index in Indonesia reached rank 77 in 2022 with a good sub-index score: 0.76 for the Online Service Index, 0.64 for the Telecommunication Infrastructure Index, and 0.74 for the Human Capital Index. The conclusion of this study shows that some of the challenges of implementing E-Government,, namely lack of data integration, minimal public participation, and lack of understanding of technical aspects and information security among Human Resources (HR), especially the State Civil Apparatus. Based on these problems, there are several research implications to improve information technology infrastructure better and more evenly distributed throughout Indonesia, namely: (1) expanding accessibility and improving digital infrastructure in Indonesia, (2) providing assistance and training to each local government and civil servants on the use and benefits of technology in the government system to provide optimal public services,  and (3) support and prioritize the integration of the National Data Center to collect all data from regions, ministries, and institutions nationally in one Big Data.